Risk Management of Daily Tourist Tax Revenues for the Maldives - Michael McAleer; Riaz Shareef; Bernardo da Veiga (Fondazione Eni Enrico Mattei (FEEM), 2005)
International tourism is the principal economic activity for Small Island Tourism Economies (SITEs). There is a strongly predictable component of international tourism, specifically the government revenue received from taxes on international tourists, but it is difficult to predict the number of international tourist arrivals which, in turn, determines the magnitude of tax revenue receipts. A framework is presented for risk management of daily tourist tax revenues for the Maldives, which is a unique SITE because it relies entirely on tourism for its economic and social development. As these receipts from international tourism are significant financial assets to the economies of SITEs, the time-varying volatility of international tourist arrivals and their growth rate is analogous to the volatility (or dynamic risk) in financial returns. In this paper, the volatility in the levels and growth rates of daily international tourist arrivals is investigated.
Keywords: G18; C32; L83; D81; 330; Small Island Tourism Economies (SITEs); International tourist arrivals; Tourism tax; Volatility; Risk; Value-at-Risk (VaR); Sustainable Tourism-@-Risk (ST@R); Internationaler Tourismus; Steueraufkommen; Risikomanagement; Insel; Malediven